2017
DOI: 10.18632/oncotarget.18963
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivated mTORC1 downregulation of FOXO3a/PDGFRα/AKT cascade restrains tuberous sclerosis complex-associated tumor development

Abstract: Hyperactivation of mammalian target of rapamycin complex 1 (mTORC1), caused by loss-of-function mutations in either the TSC1 or TSC2 gene, leads to the development of tuberous sclerosis complex (TSC), a benign tumor syndrome with multiple affected organs. mTORC1-mediated inhibition of AKT constrains the tumor progression of TSC, but the exact mechanisms remain unclear. Herein we showed that loss of TSC1 or TSC2 downregulation of platelet-derived growth factor receptor α (PDGFRα) expression was mediated by mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Subcutaneous tumors were established in nude mice as described previously 23 . Immunodeficient BALB/c nude male mice (16-18 g, 5 weeks) were purchased from Vital River Laboratories Animal Technology (Beijing, China).…”
Section: Induction Of Subcutaneous Tumors and Combination Treatment Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcutaneous tumors were established in nude mice as described previously 23 . Immunodeficient BALB/c nude male mice (16-18 g, 5 weeks) were purchased from Vital River Laboratories Animal Technology (Beijing, China).…”
Section: Induction Of Subcutaneous Tumors and Combination Treatment Wmentioning
confidence: 99%
“…Immunohistochemical analysis was performed as described previously 23 . In brief, tumor tissues were fixed in 4% paraformaldehyde and embedded in paraffin.…”
Section: Immunohistochemistry (Ihc) Analysismentioning
confidence: 99%
“…The benign feature of TSC-associated tumors has been, at least in part, attributed to the loss of Akt signaling due to either a mTORC1-dependent negative feedback regulation of Akt and the attenuation of mTORC2 signaling derived from the loss of TSC1/2 complex function [ 82 , 83 ]. More recently, other studies demonstrating that hyperactivated mTORC1-dependent Akt inhibition constrains tumor growth in TSC patients by downregulation of different signaling cascades, have been reported [ 84 , 85 ]. Jin et al also reported a hyperactivated mTORC1-independent protective effect against malignant tumor development in TSC induced by downregulation of the SOX9-OPN signaling cascade through the inhibition of Akt [ 86 ].…”
Section: Mtorc1 Signaling Pathway and Disease: The Tuberous Scleromentioning
confidence: 99%
“…The benefit of the combined treatment was also demonstrated in a TSC xenograft mouse model [ 153 ]. Wang et al showed that in both Tsc1 - and Tsc2 -null MEFs the hyperactivation of mTORC1 drives Akt inhibition through the downregulation of FOXO3a/PDGFRα pathway [ 84 ]. Rapamycin treatment led to the upregulation of PDGFRα that has been associated with the increase in tumorigenesis in Tsc1 - or Tsc2 -knockout MEFs.…”
Section: Therapeutic Strategies For Tuberous Sclerosis Complexmentioning
confidence: 99%
“…The balance of the PI3K signaling pathway is pivotal to maintain the growth and survival of the primordial follicle pool [32]; a rodent model revealed that the PI3K/AKT pathway mediated oocyte apoptosis and FoxO3a plays an important role in early follicular development [29]. Furthermore, FoxO3a was found to maintain the PTEN-PI3K-AKT-FoxO3a pathway, enabling faster follicle growth [33]. Previous researchers have found that locally produced NO and the NOS/sGC pathway might be involved in the maturation of the follicles [34,35].…”
Section: Introductionmentioning
confidence: 99%